A gift exchange relationship?: reflections on doing qualitative research with vulnerable migrants - Madziva, Roda (Policy Press, 2015)
Recent reflections on the study of forced migration stress the importance of constructing ethically sound research relationships that both respect research participants as autonomous agents and protect them from all forms of harm in the research process. Although this is important, very little research in this area has focused directly on the production of intimacy in the research process and how intimate research relationships that are produced can subsequently become the basis on which disclosures are shared and how this can contribute to both the quality of the research process and output. In this article I reflect on my intimate research relationship with Zimbabwean migrant parents who I interviewed in the United Kingdom. I argue that there is an element of (gift) exchange to intimate qualitative research encounters that yields benefits to both the researcher and the researched. In so doing, I also highlight some of the ethical dilemmas I encountered and how they were overcome